INISIASI POS PEMBINAAN TERPADU (POSBINDU) PENYAKIT TIDAK MENULAR DI WILAYAH KERJA PUSKESMAS II DENPASAR UTARA BALI - Wirakusuma, I.B.; Yuliyatni, P.C.D.; Sari, K.A.K; Ariastuti, N.L.P (Buletin Udayana Mengabdi; Vol 15 No 2 (2016): Jurnal Udayana Mengabdi, 2016)
Non communicable diseases (NCDs) are a burden for health problem in Indonesia and also in Bali. The Indonesian Ministry of Health responded by developing integrating health service (Posbindu) program for NCDs in 2013. Posbindu are expected run independently by community for NCDs screening at community health centre (CHC). The community service conducted to initiate Posbindu at CHC II North Denpasar by workshop for 70 new cadres targeted but only 36 cadres has come. The increasing of knowledge was showed by the increased of mean score from pretest to posttest (8.08 to 9.19); and proportion score ? 8 increased from 71.4% to 93.8%. This community service continued with risk factors screening for NCDs at Posbindu Kerta Sari for 100 people targeted. From 89 participants who came voluntary to Posbindu, less than 50% participants had exercise habits, salt, fatty and sweet food consumption. Based on examination, 41% participant had hypertension, 59.5% had overweight and obese, 8% had hyperglycemia and 19.1% had hypercholesterolemia. Cadre workshop is needed to be conducted routinely by Health Office. Confirmation test and treatment is needed for participants who had abnormal result in this screening.
Keywords: Posbindu, Non Communicable Diseases, Community Health Center, Initiation